2014
DOI: 10.1128/mbio.01529-14
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Influences the Maternal Transmission of the gypsy Endogenous Retrovirus in Drosophila melanogaster

Abstract: The endosymbiotic bacteria of the genus Wolbachia are present in most insects and are maternally transmitted through the germline. Moreover, these intracellular bacteria exert antiviral activity against insect RNA viruses, as in Drosophila melanogaster, which could explain the prevalence of Wolbachia bacteria in natural populations. Wolbachia is maternally transmitted in D. melanogaster through a mechanism that involves distribution at the posterior pole of mature oocytes and then incorporation into the pole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…Drosophila mauritiana females show both an increase in egg production as well as an increase in mitotic activity of germline stem cells associated with Wolbachia infection (Fast et al 2011). In D. melanogaster, Wolbachia infection reduces maternal transmission of the endogenous retrovirus gypsy (Touret et al 2014). The presence of Wolbachia also significantly affects protein abundance in D. melanogaster ovaries (Christensen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila mauritiana females show both an increase in egg production as well as an increase in mitotic activity of germline stem cells associated with Wolbachia infection (Fast et al 2011). In D. melanogaster, Wolbachia infection reduces maternal transmission of the endogenous retrovirus gypsy (Touret et al 2014). The presence of Wolbachia also significantly affects protein abundance in D. melanogaster ovaries (Christensen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect any statistically significant differences in mitochondria titer between infected and uninfected ovaries (Figure 1a,b). Other studies also found no effect of clearing Wolbachia infection on mitochondria titer in D. melanogaster ovaries (Touret, Guiguen, & Terzian, 2014) or in whole Leptopilina parasitoid wasps (Mouton, Henri, & Fleury, 2009). Second, we reasoned that if we reduce mitochondria populations that limit Wolbachia, we would expect to see an increase in Wolbachia populations.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Factor I retrotransposon RNAs produced in nurse cells migrate to the oocyte nucleus [57] and, likewise, Gypsy I RNAs produced in follicle cells traverse the perivitelline membrane to access the oocyte [6, 8, 9]. …”
Section: Resultsmentioning
confidence: 99%